Daily Lifestyle Modifications to Improve Quality of Life and Survival in Glioblastoma: A Review - Sarah Travers; N. Scott Litofsky (Brain Sciences, 2021)
Survival in glioblastoma remains poor despite advancements in standard-of-care treatment. Some patients wish to take a more active role in their cancer treatment by adopting daily lifestyle changes to improve their quality of life or overall survival. We review the available literature through PubMed and Google Scholar to identify laboratory animal studies, human studies, and ongoing clinical trials. We discuss which health habits patients adopt and which have the most promise in glioblastoma. While results of clinical trials available on these topics are limited, dietary restrictions, exercise, use of supplements and cannabis, and smoking cessation all show some benefit in the comprehensive treatment of glioblastoma. Marital status also has an impact on survival. Further clinical trials combining standard treatments with lifestyle modifications are necessary to quantify their survival advantages.